Pengaruh Motivasi, Komunikasi dan Kepemimpinan terhadap Organisasi - Dedi Kusdinar (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2017)
In principle, the progress and development of an organization / company determined among others by the performance or performance of individual work members of the organization / employees. Thus it can be said that the performance / performance of each individual work member organization / employees is very important in an organization / company. An organization / company can run or operate properly among them if followed by performance or good work performance of any human resources that exist within the scope of the organization or company. The relationship between communication and organization lies in a study focused on the people involved in achieving the organization's goals. Communication has four functions that can be used in improving job performance, namely the function of informative, regulative, persuasive, and integrative. Similarly, the role of motivation from the leadership, the higher the motivation given the leadership of the organization / company to subordinates, the higher the productivity of employees. Leaders of the company must be good at managing subordinates, so as to create a conducive working climate. This will encourage employee work productivity. Leadership is the ability and skills of a person who occupies the position as head of the work unit to influence others, especially subordinates, to think and act in such a way that through positive behavior he contributes significantly in achieving organizational goals.